Investigation of solar cell carrier lifetime using photoconductance lifetime measurements - Lye, Xin Hui (2019)
Global energy consumption has been continuously rising every year, and especially in the past decades, rapid improvement of the countries’ economy leads to an intensifying demand of energy sources. Due to finite natural resources in the world and harmfulness of burning nonrenewable energy sources, alternative sources of energy are crucial to every countries’ growth. To fulfil the growing rate of energy consumption, researches on alternatives especially on solar energy have been carried out. Solar PV system provides clean and green solar energy and thus, it captures most attention among the various alternatives. In recent years, heterojunction solar cells such as Si/PEDOT:PSS and Si/MoOx cells have become an interest of study due to their desirable electrical characteristics that contribute to the higher efficiencies in the PV cells and their lower cost and simplicity of the fabrication process. This in contrast to conventional solar cells where the fabrication process is complicated, and carried out at high temperature, thus leading to higher cost of production. Therefore, further studies on heterojunction solar cells is essential, to achieve a higher power efficiency solar cell at a lower cost of fabrication. This final year project focuses on investigation of Si/Transition Metal Oxide (Si/TMO) solar cells through studying of lifetime measurement using the reverse recovery transient measurement technique. From there, comparisons between different solar cell test results and theories based on past researches were carried out to analyse according to the experimental results obtained. The dark illuminated current density-voltage characteristics of the cells will also be studied. In this report, a thorough results analysis in relation to the solar cell photovoltaic parameters will be presented. Using the reverse recovery transient measurement, the settling time of the Si/TMO solar cells will be examined. A longer settling time reflects a larger minority carrier lifetime, which is indicative of a better efficiency solar cell. The two-diode model was applied and fitted to the dark IV curves of the Si/TMO cell, which allows us to relate the transport of the solar cell to the cell efficiency, which depends on multiple factors such as minority carrier lifetime and fill factor (FF). Lastly, I have also carried out a study on the performance of the Si/TMO solar cells with various Si-doping concentration. Some key results have been obtained through this project is that the Si/MoOx junction exhibits minority carrier storage behaviour with a significance settling time of the cells varying from 1.4 to 16.7μs. Also, assuming the p-n junction like characteristics, the cell with higher doping concentration have a reduction in carrier lifetime of 81.0μs, 44.0μs and 6.8μs, hence indicates enhanced recombination. When there is an increase in doping concentration, the shunt resistance leakage current and the recombination current are observed to increase too. In addition, the FF has an optimum value at a doping concentration at ND = 1015 cm-3 due to the conflicting effect between increasing and increasing resistance leakage current. Whereby the Voc increases due to a lower , which is in consistent with dark IV measurement and the two-diode model characteristics. As a result, a maximum power conversion efficiency (PCE) of 9.5% occurs for the cell with ND = 1015 cm-3 were found.